Relational Petri Nets with start/stop place - Karci, A; Arslan, A (Ieee Computer Soc, 2000)
We have adapted Petri nets and functional dependencies amongst objects to parallel rule languages. After this adaptation, the yielded Petri net - we will call it Relational Petri Nets (RPNs) with Start/Stop Place - is analysed in this paper. Liveness, reversibility, no conservation and boundedness in practice, consistency, strongly connected of this kind of net have been specified in this work. The properties of transitions are also analysed in this work.
7th International Conference on Parallel and Distributed Systems Workshops (ICPADS 2000) -- JUL 04-07, 2000 -- IWATE, JAPAN